2010
DOI: 10.1160/th09-08-0527
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of platelet function tests and thromboxane metabolites to evaluate aspirin response in healthy individuals and patients with coronary artery disease

Abstract: Individualised antiplatelet therapy and platelet function testing have attracted considerable clinical interest, but several aspects of test performance have not been thoroughly evaluated. We investigated repeatability and concordance of light transmission aggregometry (LTA) induced with arachidonic acid (AA) 1.0 mM, PFA-100 induced with collagen/epinephrine, multiple electrode aggregometry (MEA) induced with AA 0.5 or 0.75 mM and VerifyNow Aspirin. Patients with stable coronary artery disease (n=43) and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(25 citation statements)
references
References 49 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…In addition, platelet function assays may have suboptimal reproducibility. 27 As such, previously reported variability in antiplatelet effects of clopidogrel is partly explained by CYP2C19 polymorphisms. 28,29 Therefore, we measured CYP2C19 polymorphisms that may affect clopigogrel-induced platelet inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, platelet function assays may have suboptimal reproducibility. 27 As such, previously reported variability in antiplatelet effects of clopidogrel is partly explained by CYP2C19 polymorphisms. 28,29 Therefore, we measured CYP2C19 polymorphisms that may affect clopigogrel-induced platelet inhibition.…”
Section: Discussionmentioning
confidence: 95%
“…In parallel, a number of different studies have shown platelet function assay results to lack correlation and agreement among themselves, thus identifying different patients as poor responders to aspirin and having different determinants of response. 37,75,76 Which platelet function assay, if any, is the most clinically predictive of future major adverse cardiovascular events remains to be established. 77 As a consequence, the natural history of aspirin resistance remains somewhat uncertain.…”
Section: Platelet Function Assaysmentioning
confidence: 99%
“…The term aspirin resistance has also been used in the laboratory context. Here, aspirin resistance describes persistent platelet reactivity in vitro , despite the use of aspirin, measured by various platelet function tests such as measurement of serum and urinary thromboxane metabolites, and AA-induced platelet aggregation, collagen-induced platelet aggregation, or ADP-induced platelet aggregation [35,36]. One limitation of the assessment of the various functional indexes of platelet capacity that can be measured ex vivo with in-vitro tests is the largely unknown translational relevance to the actual occurrence of platelet activation and inhibition in vivo [37].…”
Section: Variability In Platelet Response To Aspirinmentioning
confidence: 99%